Optimum Savings and Utility Maximization Over Time - Tinbergen, J. (Econometrica, 1960)
The problem dealt with in this article is whether we can indicate, with the help of measured economic concepts, the rate of savings–as a function of time–which maximizes utility over time. The author believes that his attempt has been unsuccessful, but hopes that the nature of the difficulties encountered may be of some help in future attempts to solve this problem. A problem regarding the most important decision to be taken for any development program.